Plans to Obtain Cargo for Friend Ship Formulated - Cleek, John L. (Unknown)
Plans for collecting food and clothing for consignment to France, Italy, and Greece aboard the Golden Bear, the training ship of California Maritime Academy which is scheduled to leave the home port of Morrow Cove on January 15th, on the first leg of a memorable voyage as Friend Ship, took on form last evening at a conference called by Ernest Wichels, head of the Vallejo committee. The meeting was highlighted by a report from Commodore Russell M. Ihrig following a conference in Sacramento with Governor Earl Warren and other state officials who are giving full cooperation to the movement to dispatch 1,200 tons of food, and clothing. Governor Warren informed Com. Ihrig that Maurice Sparling, State Bank Commissioner has accepted the chairmanship of the state committee and already has committees arranging for the collection for food and clothing.